Short communication: First record of Arapaima gigas (Schinz, 1822) (Teleostei: Osteoglossomorpha), in the Brantas River, Sidoarjo, East Java, Indonesia - Mohamad Fadjar; R Adharyan Islamy; Endang Yuli Herawati (Society for Indonesian Biodiversity, 2019)
Abstract. Fadjar M, Islamy RA, Herawati EY. 2019. Short communication: First record of Arapaima gigas (Schinz, 1822) (Teleostei: Osteoglossomorpha), in the Brantas River, Sidoarjo, East Java, Indonesia. Biodiversitas 20: 3527-3531. The arapaima (= Arapaima gigas) is the largest freshwater fish in the Neotropical region, obligate air-breathing fish that known to reach up to 3 m - 3.90 m in length and 200 kg in weight endemic to the Amazon basin. Arapaima gigas is giant osteoglossomorph and obligate air?breathing fish and also a native species of the Amazon basin. We present the first record of Arapaima gigas (Schinz, 1822) in Brantas River, Sidoarjo, East Java, Indonesia with diagnostic meristic and morphometrics of the specimens analyzed following Stewart method. Herein, it recorded from the Brantas River basin. This record based on the finding of one live specimen on the tributary of Brantas River basin, and in situ observation of juveniles and adults in the river).